One-pot hydrothermal synthesis of CdS–CuS decorated TiO2 NTs for improved photocatalytic dye degradation and hydrogen production. Issue 21 (1st November 2021) - Hou, Junwei; Huang, Bingxuan; Kong, Lingcong; Xie, Yu; Liu, Yansheng; Chen, Mengmeng; Wang, Qingyao
Abstract: TiO2 nanotube arrays (TiO2 NTs) were regarded as the outstanding semiconductors for the photocatalytic application in waste water treatment and H2 generation, and CdS nanoparticles as the visible light sensitizers were traditionally used to enhance the photocatalytic performance. In this paper, CdS–CuS co-sensitizers were deposited on TiO2 NTs by one-pot hydrothermal method, and the Cu/Cd ratio was changed to adjust the hybrid photocatalyst composition and electron transfer. The photocatalytic data indicated that suitable CdS–CuS composition could effectively enhance the photocatalytic pollutant removal and photocurrent/H2 evolution and the hybrid photocatalyst also exhibited the high stability by the inhibition of CdS photocorrosion. The p-n heterojunction construction of TiO2 NTs/CdS–CuS benefited the solar response, photoelectron separation and photocatalytic reaction, and the photocatalytic mechanism and photoelectron transfer were investigated. The p-n heterojunctional photocatalyst is supposed to apply in environmental remediation and new energy development.